AKUNTANSI DALAM ERA URBAN BERDASARKAN PERSPEKTIF PANCASILA DAN AL-QURAN - Geovani Geovani; Erina Sudaryati (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2018)
Urban society is a group of social creatures that need each other in a common life called the community. Accounting as a science is used every day and every moment in human life. Pancasila is also proved to have a meaning related to that has been written in the Quran as the holy book of Muslims. This paper will discussed about accounting in the urban era based on the point of view of Pancasila and Al-Quran. This research is based on the ontology aspect of the relitas that occurs in Indonesian urban society.